Evaluation of Diagnostic Methods for Complications of Meckel's Diverticulum: A Retrospective Analysis - Binici, Serhat; Yesilyurt, Değercan; Eryılmaz, Iklil; Aslan, Fırat; Tahiro?lu, Veysel; Be?er, Burhan (Yuzuncu Yil Universitesi Tip Fakultesi, 2025)
Meckel's diverticulum (MD) is the most common congenital abnormality of the small intestine, often asymptomatic but occasionally presenting with acute abdominal symptoms that can mimic other conditions such as appendicitis, perforated peptic ulcer, or bowel obstruction. This study reviews eight cases of MDs diagnosed and treated surgically, highlighting the clinical presentations, diagnostic challenges, and surgical outcomes. This retrospective study included seven male and one female patients aged 18 to 43 who presented to the emergency department with symptoms of acute abdomen. Imaging studies, including abdominal computerised tomography (CT) scans and ultrasonography, were utilized to assess the patients. Laparoscopic surgery was performed in six cases, while two cases required open surgery. Surgical management involved excision of the Meckel's diverticulum using a line ar stapler. All patients presented with severe abdominal pain, and physical examination revealed signs of acute abdomen such as tenderness, guarding, and rebound tenderness. Initial diagnoses included appendicitis, perforated peptic ulcer, mechanical bowel obstruction, and foreign body ingestion. Intraoperative findings confirmed the presence of Meckel's diverticulum in all cases. The excision of the diverticulum was successfully performed, and all patients had uneventful postoperative recoveries. The mean hospital stay was 3.75 days, and no major complications were observed.Meckel’s diverticulum can present with a wide range of symptoms, often mimicking other abdominal conditions, making early diagnosis and appropriate surgical intervention essential. Laparoscopic surgery is a safe and effective approach for the excision of Meckel's diverticulum, with favorable outcomes and minimal complications. Prompt recognition and treatment are key to ensuring optimal patient outcomes. © 2025, Yuzuncu Yil Universitesi Tip Fakultesi. All rights reserved.
Keywords: Acute abdomen; Laparoscopy; Meckel's diverticulum